PUASA MENURUT AJARAN AGAMA HINDU ( PERSPEKTIF BUDAYA JAWA ) - Titin Sutarti (Lembaga Penerbit Sekolah Tinggi Hindu Dharma Klaten, 2019)
Fasting in Javanese various types, fasting or asceticism can be done in many ways, many models and forms. Tapa brata, both physical and mental, cannot be separated because it is an integrated whole. Fasting has a very good and big effect on the body and mind. Fasting in a supernatural way alters the physical and etheric molecular systems of the body and increases its vibrations so as to make the body more sensitive to supernatural energy or power, while at the same time trying to awaken one's sixth sense ability. When a person is accustomed to fasting, the vibrations of the physical and etheric body will increase so that all poisons, negative energy and negative etheric beings in his body will come out and his body will be clean. The direct or indirect impact of the implementation of fasting on the physical or spiritual in the long term or short term, for the individual or the environment, namely; Increased physical health, psychology, and spiritual, Increased sensitivity and concern for others, Increased adherence to Hyang Widi. Fasting intends to restrain the pleasures, desires or passions that are not good and unwise in life, and galvanize yourself to get the 'endurance' of body and soul in the face of the waves of life. Peace in life can be seen from the attitude of someone who lives this life in moderation, this life is lived proportionally, in harmony with what is truly a necessity of life, and does not exceed the limits of appropriateness or fairness.